Tasawuf sebagai Solusi Krisis Spiritual dalam Masyarakat Modern - Hasibuan, Qori Ananda Azhari; Nasution, Syawaluddin (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study aims to examine the role of Sufism as a spiritual remedy to the existential crisis faced by modern society. The phenomenon of inner emptiness, psychological distress, and moral degradation poses serious challenges in a materialistic and rationalistic era. In this context, Sufism offers a spiritual approach emphasizing self-purification, closeness to God, and the cultivation of virtuous character. Employing a qualitative literature review method, data were collected from classical and contemporary Sufi texts, scientific journals, articles, and prior research findings. The data were analyzed using Miles and Huberman’s interactive analysis model, which includes data reduction, data display, and conclusion drawing. The findings reveal that Sufism plays a significant role in enhancing modern society’s spiritual and emotional resilience. Core values such as sincerity (ikhlas), patience (sabr), asceticism (zuhd), trust in God (tawakkul), and self-reflection (muhasabah) remain relevant for alleviating inner turmoil and providing life with deeper meaning. In educational contexts, integrating Sufism can balance intellectual and spiritual dimensions among learners. This study concludes that Sufism is not merely a personal religious practice but also a cultural and educational approach that addresses contemporary spiritual crises holistically.‎